FACTORS ASSOCIATED WITH OCCURRENCE OF PNEUMONIA AMONG CHILDREN UNDER FIVE YEARS AT ISHONGORORO HEALTH CENTRE IV IN IBANDA DISTRICT: A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Semakura , Jibril (Student’s Journal of Health Research Africa, 2023)
Background: Pneumonia is an infection of the lungs, caused by among other etiologies, bacteria, or viruses. It is an infection of the lung parenchyma and is caused by a wide variety of organisms in pediatric patients. The study focussed on assessing the socio-demographic, environmental, and health-related factors associated with pneumonia among children under five years. Methodology: A descriptive cross-sectional study design was used using a structured questionnaire amongst 85 respondents who were selected using a systematic sampling method to participate in the study. Results: From the study, the majority 50% were married, most 45 had attained primary level, the majority 62% of the respondents were from rural areas, the majority 43% were peasants, and 57% had more than 3 children, Results showed that 475% agreed that there was a window on respondents’ house and more on their house, majority 78% of the respondents were leaving their windows open daily, majority 28(70%) of the respondents were having their household near the street, majority 68% of the respondents were using wood for cooking, Conclusion: According to the study results and discussions, it was revealed that factors such as mothers’ age, parents’ level of education, and Household monthly income levels were associated with pneumonia among children aged five years and below Furthermore kind of fuel respondents use for cooking such as wood, respondents were not leaving their windows open daily, the house has less than two windows, not having a window on their house were associated with pneumonia among children aged five years and below. Recommendation: The researcher recommends that there should be an organized effort to mobilize communities on health benefits and use kitchens with enough smoke escape roots like windows and/or chimneys and control programs should focus on treatment and prevention of severe pneumonia among children.